An Empirical Evaluation of a Summer Bridge Program on College Graduation at a Small Liberal Arts College. (February 2023) - Greer, Christiaan; Chi, Cheng; Hylton-Patterson, Nicole
This longitudinal study evaluated the efficacy of a summer bridge program (SBP) and other support services on college graduation rates at a small liberal arts school in Purchase, NY. Financially disadvantaged students (n = 136) receiving a scholarship and a summer bridge curriculum within the Manhattanville Achievement Program were compared to students who received Pell Grants but did not receive the summer bridge program (n = 1, 293) from 2008–2014. Outcomes assessed included graduation at 4 years and 6 years post-enrollment, GPA, and demographic characteristics of those who were more likely to graduate. Results indicated that enrollment in the SBP predicted a greater likelihood to graduate at 4 and 6 years while enrollment in the SBP did not predict higher GPA at either 4 or 6 years post-enrollment. Consistent with national trends, men were less likely to graduate than women. Implications of the findings are discussed.